Formation of magnesium hydrosilicate nanomaterials and its applications for phosphate/ammonium removal. Issue 17 (2nd September 2018) - Yu, Rongtai; Liu, Feng; Ren, Hongqiang; Wu, Jichun; Zhang, Xuxiang
ABSTRACT: Nanomaterials of magnesium hydrosilicate Mg3 Si2 O5 (OH)4 were developed for phosphate and ammonium recovery from wastewater in virgin, which had the structure of diffuse interlamellar order, and synthesized under hydrothermal conditions at temperatures of 200°C for 36–72 h from mixtures of magnesite and zeolite as mineralizers. The amount of magnesium released has gone up to 48 mg/g by magnesium hydrosilicate, which was increased with the increase in the weight ratio of magnesite:zeolite. When magnesium hydrosilicate was used to adsorb phosphate and ammonium, electrostatic adsorption was not a dominant mechanism, the adsorbing capacity of phosphate was about 19 mg/g, and the simultaneous adsorbing capacity of ammonium was 7.8 mg/g.